The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.seppur.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sub-critical long-term operation of industrial scale hollow-fibre membranes in a submerged anaerobic MBR (HF-SAnMBR) system

Abstract: ElsevierRobles Martínez, Á.; Ruano García, MV.; Ribes Bertomeu, J.; Ferrer, J. (2012). Sub-critical long-term operation of industrial scale hollow-fibre membranes in a submerged anaerobic MBR (HF-SAnMBR) ngerobma@upv.es AbstractThe aim of this study was to evaluate the long-term performance of hollow-fibre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
(19 reference statements)
1
25
0
1
Order By: Relevance
“…Nevertheless, these fluxes are still low compared with those obtained in the aerobic membrane bioreactor (Lin et al, 2013;Smith et al, 2012). Robles et al, (2012) also reported a high flux of around 13-10 L/m 2 h, with solid concentrations of between 10-25 g/L, and temperatures in the range of 33-20ºC with an average specific gas demand per membrane area of 0.23 Nm 3 /m 2 h.…”
Section: Biochemical Methane Potential Assay Of Accumulated Particulamentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, these fluxes are still low compared with those obtained in the aerobic membrane bioreactor (Lin et al, 2013;Smith et al, 2012). Robles et al, (2012) also reported a high flux of around 13-10 L/m 2 h, with solid concentrations of between 10-25 g/L, and temperatures in the range of 33-20ºC with an average specific gas demand per membrane area of 0.23 Nm 3 /m 2 h.…”
Section: Biochemical Methane Potential Assay Of Accumulated Particulamentioning
confidence: 84%
“…Although the authors suggested that, the chemical cleaning of the membrane would have been desirable once quarterly. Nevertheless, Robles et al, (2012) reported that, no chemical cleaning was conducted during system operating for more than one year.…”
Section: Biochemical Methane Potential Assay Of Accumulated Particulamentioning
confidence: 99%
“…o Chemical reagents used to clean membranes: According to Judd and Judd [6] and previous experiments (see, for instance, [28]), 9.5 months can be set as the interval for membrane cleaning with chemicals when operating under critical filtration conditions. Therefore, in this study, the membrane chemical cleaning frequency ranged from 2 months (operating at J20 = 120% of JC20) to 18 months o Membrane replacement cost: As regards membrane lifespan, the cost of replacing the membrane was contemplated in order to evaluate the entire lifecycle cost of the system.…”
Section:  Operating Cost (Oc)mentioning
confidence: 99%
“…This is considered to be one of the main constraints on membrane operating because it can result in a high membrane fouling propensity and therefore high energy demand for membrane scouring by gas sparging [7].…”
Section: Introductionmentioning
confidence: 99%